SEAGRASS ORGANIC CARBON STOCK IN ALANG-ALANG BEACH, KARIMUNJAWA - Patria Theda Ramadanti; Nurul Latifah; Agus Hartoko; Sigit Febrianto; Hadi Endrawati; Diah Ayuningrum (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
The research was conducted in Alang-alang beach, Karimunjawa, in December 2019. The research method used descriptive explorative. Sampling was carried out at 18 points on Alang-Alang beach using a purposive sampling method with the help of line transects and transect quadrants. Observation method seagrass using seagrass watch. The results of this study indicate that found four different types of seagrasses were in Alang-alang beach, Karimunjawa, namely Enhalus acoroides (Ea), Thalassia hemprichii (Th), Cymodocea rotundata, (Cr) and Cymodocea serrulata (Cs), with a kind of seagrass that dominate these waters are the type of Thalassia hemprichii. The highest seagrass density is on line 6, which is 256 shoot m-2 with Th as a dominant, and line 5 (238 shoot m-2) with Cr as a dominant. While, the lowest density is on line 1 (28 shoot m-2) with Ea as a dominant. In this research above ground biomass (1.35 g m-2) has a higher value than below-ground biomass (1.25 g m-2), with Ea having the highest biomass, while Cr has the lowest, but Cr has a high density. Therefore, the highest organic carbon stock (OCS) is Ea (103.216 g Corg m-2), while the seagrass species that has the smallest OCS is Th (61.562 g Corg m-2). The average organic carbon stock obtained was 35.07 g Corg m-2.